Diet-Induced Maternal Obesity Alters Insulin Signalling in Male Mice Offspring Rechallenged with a High-Fat Diet in Adulthood. - Thaís de Fante; Laís Angélica Simino; Andressa Reginato; Tanyara Baliani Payolla; Débora Cristina Gustavo Vitoréli; Monique de Souza; Márcio Alberto Torsoni; Marciane Milanski; Adriana Souza Torsoni (PLoS ONE, 2016)
Modern lifestyle has resulted in an increase in the prevalence of obesity and its comorbidities in pregnant women and the young population. It has been well established that the consumption of a high-fat diet (HFD) has many direct effects on glucose metabolism. However, it is important to assess whether maternal consumption of a HFD during critical periods of development can lead to metabolic changes in the offspring metabolism. This study evaluated the potential effects of metabolic programming on the impairment of insulin signalling in recently weaned offspring from obese dams. Additionally, we investigated if early exposure to an obesogenic environment could exacerbate the impairment of glucose metabolism in adult life in response to a HFD. Swiss female mice were fed with Standard Chow (SC) or a HFD during gestation and lactation and tissues from male offspring were analysed at d28 and d82. Offspring from obese dams had greater weight gain and higher adiposity and food intake than offspring from control dams. Furthermore, they showed impairment in insulin signalling in central and peripheral tissues, which was associated with the activation of inflammatory pathways. Adipose tissue was ultimately the most affected in adult offspring after HFD rechallenge; this may have contributed to the metabolic deregulation observed. Overall, our results suggest that diet-induced maternal obesity leads to increased susceptibility to obesity and impairment of insulin signalling in offspring in early and late life that cannot be reversed by SC consumption, but can be aggravated by HFD re-exposure.